2022
DOI: 10.3390/su142013071
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Bleaching Earth: The Green Solution for Rapeseed Oil Producers

Abstract: The main purpose of the presented research is to characterize the relationship between the amount of bleaching earth used in the bleaching process of rapeseed oil and the efficiency of this process. Changes in the content of chlorophyll and carotenoid pigments were examined using spectrophotometric and colorimetric methods. The process was carried out on a plate filter with different thicknesses of bleaching earth (BE) layers (1–3% in relation to the amount of oil). On the basis of the conducted research, a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The increase in the a* parameter was solely associated with the breakdown of chlorophylls, which decompose under the influence of UV radiation. However, the simultaneous change in both parameters resulted from slower carotenoid degradation, as shown in previous studies [1]. Based on the above research, it can be concluded that cold-pressed vegetable oils are best stored away from sunlight.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The increase in the a* parameter was solely associated with the breakdown of chlorophylls, which decompose under the influence of UV radiation. However, the simultaneous change in both parameters resulted from slower carotenoid degradation, as shown in previous studies [1]. Based on the above research, it can be concluded that cold-pressed vegetable oils are best stored away from sunlight.…”
Section: Resultssupporting
confidence: 69%
“…Due to their health-promoting properties, vegetable oils are essential to a balanced human diet [1][2][3][4]. Apart from food applications, vegetable oils and their derivatives are also used in synthesizing polymeric materials, robotics, and 3D printing [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The bleaching methodology was developed based on Marcinkowski et al [19] and Kwasnica et al [9] and patent method PL 232781. The bleaching process was performed in two stages.…”
Section: Low-temperature Bleachingmentioning
confidence: 99%
“…The color of vegetable oils is determined by the carotenoid and chlorophyll pigments [18]. Excess chlorophyll pigments are responsible for faster oil oxidation, bitter taste, and dark green color [19]. Therefore, removing chlorophyll pigments by bleaching will positively affect the sensory properties and extend the shelf life of vegetable oils.…”
Section: Introductionmentioning
confidence: 99%